Effect of Music Therapy on Blood Pressure Reduction: Literature Review - Joni Siahaan; Rosida Rosida; Chandra Rahmadi (School of Health Sciences Al-Ma'arif, 2025)
Hypertension is a major risk factor for cardiovascular disease, morbidity, and mortality worldwide. Music therapy provides many benefits for people with hypertension such as lowering blood pressure, as well as reducing anxiety, stress, and pain. This study aims to assess the effectiveness of music therapy in providing beneficial effects for elderly people with hypertension. the writing of this article analysis is based on literature review data base that is searched using Google Scholar, elseiver, and Pubmed websites between 2016-2023. Article search method with PRISMA method. Keyword search ((((((music) OR (music therapy)) OR (sound therapy)) AND (hypertension)) OR (high blood pressure)) OR (cardio-vascular)) AND (Supplementary). The standards desired by the author include: research that explores music therapy variables on blood pressure reduction in adults Total articles obtained were 10 that met the research topic. Based on the analysis of 10 articles, it was found that music therapy can effectively reduce systolic blood pressure diastolic blood pressure. Listening to music is strongly associated with a clinically significant decrease in systole blood pressure and diastole blood pressure so it is very effective in the application of complementary nursing interventions in patients with hypertension.